Adrenocortical carcinoma extending into the inferior vena cava in a patient with right kidney agenesis: Surgical approach and review of literature - Meniconi, Roberto Luca (Elsevier, 2012)
INTRODUCTION: Adrenocortical carcinoma (ACC) is a rare malignancy with a poor prognosis and the association with tumor thrombus into the inferior vena cava (IVC) is not common. The best treatment is represented by radical surgery. PRESENTATION OF CASE: We describe a case of a large ACC of the left adrenal gland extending into the IVC through the left renal vein in a young patient with agenesis of the right kidney and signs of acute renal failure. A midline laparotomy was performed, subsequently extended by a left thoracophrenotomy through the 7th intercostal space in order to control the proximal surface of the mass and the thoracic aorta. The tumor was completely excised preserving the kidney, and thrombectomy was performed by a cavotomy with a temporary caval clamping, without cardiopulmonary by-pass (CPB). DISCUSSION: We discuss surgical approaches reported in literature in case of ACC with intracaval extension. The tumor must be completely resected and the thrombectomy can be performed by different approaches: cavotomy with direct suture, partial resection of caval wall without reconstruction, resection of vena cava with graft reconstruction. These procedures could require a CPB, with an increased mortality. In our case we preserved the kidney and a thrombectomy without CPB was performed. CONCLUSION: Intracaval extension of ACC does not represent a contraindication to surgery. The best treatment of intracaval thrombus should be the cavotomy with direct suture. The CPB is not always required. In presence of renal agenesis, the preservation of the kidney is mandatory.